Phase stability and microstructure morphology of microwave-sintered magnesia-partially stabilised zirconia. Issue 3 (1st February 2021) - Chen, Guo; Li, Qiannan; Ling, Yeqing; Zheng, Hewen; Chen, Jin; Jiang, Qi; Li, Kangqiang; Peng, Jinhui; Omran, Mamdouh; Gao, Lei
Abstract: In this work, microwave heating approach was introduced into the preparation process of zirconia materials to overcome the tricky technical defects during the traditional electric arc furnace method. Magnesia-partially stabilised zirconia (MgO-PSZ) with enhanced stability and a uniform microstructure was prepared via microwave heating of a ZrO2 sample manufactured by the electric arc furnace method. The effects of microwave heating on the phase stability properties, microstructure, and surface morphology of the prepared MgO-PSZ sample were evaluated via X-ray diffraction (XRD), Raman spectroscopy, Fourier transform infrared (FT-IR) spectroscopy, and Scanning electron microscopy, and the obtained results suggested that the stability rate of the MgO-PSZ sample improved from the initial value of 81.19%–94.82% after microwave heating at 1300 °C for 1 h. As a result of the martensitic conversion of ZrO2 material, the m-ZrO2 diffraction peaks were suppressed at the same time. Additionally, a similar changing trend was noticed in the XRD pattern, Raman spectrum, and FT-IR spectrum, indicating a decrease in the m-ZrO2 phase content in the microwave treated products. Furthermore, the microstructure on the surface of the microwave-sintered MgO-PSZ sample was improved in contrast to the raw MgO-PSZ sample, and became relatively more uniform and smooth. This study determined the optimal microwave heating conditions for the preparation of MgO-PSZ material with enhanced performance, and can provided as a good foundation for developing the further related research on zirconia materials preparing by microwave heating technology.